The Interpretation of Least Squares Regression With Interaction or Polynomial Terms - Bernhardt, Irwin; Jung, Bong S. (The Review of Economics and Statistics, 1979)
l'Evolution de Coefficients Input-Output, Economic Applique 16 (1) (1963). Parikh, Ashok, and R. Edwards, Estimation of Gross Domestic Output and Employment by Sectors through Input-Output SSRC Report, unpublished, 1975. Theil, Henri, Applied Economic Forecasting (Amsterdam: North-Holland Publishing Company, 1966). Theil, Henri, and C. B. Tilanus, Demand for Production Factors and the Price Sensitivity of Input-Output Predictions, International Economic Review 5 (1964), 258-272. Tilanus, C. B., Input-Output Experiments, The Netherlands, 1918-61 (Rotterdam: Rotterdam University Press, 1966). United Nations, Input-Output Tables and Analysis, Studies in Methods, series F, no. 14, rev. o (New York: United Nations, 1973).